Perancangan Konsep Mesin Press Hidrolik Sampah Botol Plastik Kapasitas 10 Ton Berbasis Kontrol PLC - Hildan Tsabit Nur Rofi Hildan Tsabit Nur Rofi; Iwan Agustiawan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The increasing volume of plastic bottle waste from various activities causes obstacles in management and storage, so an automatic compactor machine is needed that is able to reduce the volume of waste effectively and increase transportation efficiency. This study aims to produce a concept design for a hydraulic press machine for plastic bottle waste with a pressing force capacity of 10 tons equipped with an automatic control system based on Programmable Logic Controller (PLC). This research is a design research (engineering design research) that aims to produce a concept for a hydraulic press machine for plastic bottle waste with a capacity of 10 tons based on Programmable Logic Controller (PLC) control. The design method used refers to the Quality Function Deployment (QFD) approach to translate user needs into product technical specifications. Data analysis techniques are carried out qualitatively and quantitatively, through interviews with Plastavfall Solution to collect data. Then using literature studies by reviewing journals, books and previous research related to hydraulic systems, PLCs and QFD methods. Based on the design process, a House of Quality is obtained that describes the relationship between the technical specifications of the machine plan with the needs and desires of consumers, the selected machine concept presented in the form of a functional description of the machine concept, and 3D SolidWorks drawings. This design process was carried out by utilizing Automation Studio Software and Zelio Soft 2 Software.